Radar automatic target recognition (ATR) and non-cooperative target recognition (NCTR) - Blacknell , David; Blacknell, David; Griffiths, H. (Hugh), 1956- (London, United Kingdom The Institute of Engineering and Technology, 2013)
The ability to detect and locate targets by day or night, over wide areas, regardless of weather conditions has long made radar a key sensor in many military and civil applications. However, the ability to automatically and reliably distinguish different targets represents a difficult challenge. This book presents an overview of the state-of-the-art and continuing challenges of radar target recognition.
Includes bibliographical references and index.
Keywords: Radar; Radar targets